Tuberculosis treatment outcomes of non-citizen migrants: Israel compared to other high-income countries - D. Chemtob; E. Ogum (BMC, 2020)
Abstract Background: In TB low incidence countries, the outcome of TB treatment among non-citizen migrants from endemic countries affects ability to eliminate TB. This study compares TB treatment outcomes among non-citizen migrants in select pre-elimination country based on their policies for non-citizen migrant TB patients in order to determine how policy affects TB outcomes. Methods A literature review was conducted via PUBMED, MEDLINE (2000-2017) on TB policy among non-citizen migrants and treatment outcome. Treatment outcome among migrants diagnosed in Israel during 2000-2014 was analysed. Results In total, 18 publications met the inclusion criteria. All the countries reviewed except the United States offered free TB treatment to undocumented migrants. Successful TB treatment outcome for non-citizen migrants in Israel was 87%, the Netherlands was 90.7%, the UK was 82.1%, and outcomes in the US and Australia were not published. Conclusions There is a need to standardize results based on international definitions of migrants, asylum seekers, and refugees in order to determine status-specific barriers and to facilitate international comparisons. Policies insuring free access to TB care for non-citizen migrants are an important element for TB elimination in low incidence countries.